NODIRA MELODIES OF NAVOI - Imomaliyeva, Musharrafxon (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
The article shows the influence of Alisher Navoi’s heritage on the work of Mohlaroyim Nadira, as well as the example of Navoi-like melodies in the work of the poetess, and her introduction to the poet’s ghazal. Although she lived in a very complicated political life, the poet made a great contribution to the development of our classical literature of the 19th century, gathered around her people who enjoyed art, and educated them. As a result, female poets also actively participate in literary life in Kokand. They also created divans, their works were included in collections, tazkiras, their recognition and notable aspects are mentioned in the article. The fact that Nodirabegim is the owner of high artistic thinking, he is also famous as a statesman with his active social activities, and at the same time, the aspects of Nodirabegim’s lyrics, rich in deep and philosophical observations, are presented in a detailed study.